DINAMIKA GROUPTHINK DALAM PENGAMBILAN KEPUTUSAN TIM LINTAS BUDAYA PERSPEKTIF INDONESIA - Ritonga, Ahmad Rasyid; Mailin, Mailin; Rubino, Rubino (STIT Ibnu Rusyd Tanah Grogot, 2025)
This study aims to analyze the dynamics of the groupthink phenomenon in the context of decision-making by cross-cultural teams in Indonesia. Groupthink refers to the psychological conditions that arise in highly bonded groups, in which the pressure to reach an agreement can hinder the logical assessment of alternatives. The methodology used in this study is a qualitative approach with a focus on case studies in several multicultural organizations in Indonesia. Data collection was carried out through in-depth interviews, participatory observations, and analysis of relevant documents. The findings of this study show that cultural factors have a significant influence on the decision-making process. Values such as collectivism, hierarchy, and social harmony contribute to the occurrence of the groupthink phenomenon. In addition, cultural diversity within a team can serve as a driver or barrier in overcoming the negative impact caused by groupthink, depending on how those differences are managed in the context of the team. This study recommends several mitigation strategies to improve the quality of decision-making in cross-cultural teams in Indonesia. Among these strategies are raising awareness of the potential of groupthink, strengthening inclusive leadership, and encouraging open communication. By implementing these steps, it is hoped that the team can be more effective in managing group dynamics and produce better decisions.